ممارسة الأنشطة البدنية والرياضية خلال حصة التربية البدنية والرياضية ودورها في التقليل من الخجل الإجتماعي لدى تلاميذ المرحلة الثانوية - حويلي, أمينة; قادري, صابرين (My University, 2020)
Summarization Practicing physical and sports activities during the physical and sports education session and its role in reducing social shyness among high .school students This study aims to practice physical and sports activities during the physical education class and its role in reducing social shyness among secondary school students, the two students assumed that physical and sport activities during the physical education class have an effective role in reducing social shyness among high school students. Verifying the validity of our hypotheses. The measure of social shyness (Jones and Russell), which measures the trait of shyness, was deliberately distributed to secondary school pupils in the two districts of Muhammadiyah and Al Kheithir. The sample size in the current study was: 210 pupils and students, which constitutes (14%) of the total community of number 1433 pupils and students are divided into two groups, the first is practicing forphysical and sports activities and the second is not practicing for physical and sports activities, where the sample consists of 157 students practicing for physical and sports activities and 53 pupils not practicing physical and .sports activities After the statistical treatment, the two students concluded that practicing physical and sporting activities has an effective effect in reducing social shyness among students at the secondary education stage during that sensitive stage in their lives, in addition to its effective role in achieving psychological balance and getting rid of the excess energy that people feel in general and adolescents Especially, as the latter needs a group of sports activities through which he can spend this energy. Accordingly, the two students proposed some solutions and programs that focus towards focusing on media awareness programs on the use of educators and teachers in the method of guidance and guidance in dealingwith adolescents to reduce their sense of shame, in addition to encouraging them to engage in meaningful discussions about what relates to their daily lives to find linguistic and intellectual contact between them
MEPS2020-40
Keywords: ممارسة الأنشطة البدنية كالرياضية; حصة التربية البدنية كالرياضية; الخجل الإجتماعي; تلاميذ المرحلة الثانوية